El efecto de la experiencia sobre la reestructuración de los sistemas de creencias de Quine y Wittgenstein - Ariso, José María (Logos. Anales del Seminario de Metafísica, 2009)
After describing the main lines of the systems of beliefs Quine and Wittgenstein expounded, I make reference in this paper to the similarities and differences Pieranna Garavaso and Danièle Moyal-Sharrock find between both systems. Through the critique of these interpretations, I will place emphasis on one aspect of the Wittgensteinian system of beliefs which, from my point of view, is of highest importance. I am referring specifically to the possibility of revising even the most basic beliefs of this system. The analysis of this problem will lead me to approach another very important question, i. e.: would the revision of our most fundamental beliefs mean that the concept of humanity itself lose all sense?
Keywords: Wittgenstein; Quine; Belief; System; Mankind